1988
DOI: 10.1007/bf02370107
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of N2 fixation in maize (Zea mays L.)—ricebean (Vigna umbellata [Thunb.] Ohwi and Ohashi) intercrops

Abstract: The yield of N in maize (Zea mays L.) and ricebean (Vigna umbellata [Thunb.] Ohwi and Ohashi) were compared on a Tropoqualf soil in North Thailand in 1984 and 1985. Both species were grown in field plots in monoculture or as intercrops at a constant planting density equivalent to 8 maize or 16 ricebean plants per m 2. The contribution of symbiotic N 2 fixation to ricebean growth was estimated from measurements of the natural abundance of ~SN (6~N) in shoot nitrogen and from analysis of ureides in xylem sap va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

1990
1990
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(35 citation statements)
references
References 26 publications
0
35
0
Order By: Relevance
“…In addition, where soil (one being a legume) N fettility is high, legumes in the field thrive without fixing atmospheric N 2 , so high levels of soil nitrate can be a potent inhibitor of N 2 fixation (Streeter 1988). In intercropping systems, competition for soil mineral N between legumes and cereals can result in stimulation of biological N 2 fixation and increased harvest of total interplanted crops (Rerkasem et al 1988;Chandel et al 1989;Peoples et al 1995;Elabbadi et al 1996). Both the competition of N from intercropping maize and the improvement of Fe nutrition of peanut could promote N 2 fixation of peanut in this intercropping system.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, where soil (one being a legume) N fettility is high, legumes in the field thrive without fixing atmospheric N 2 , so high levels of soil nitrate can be a potent inhibitor of N 2 fixation (Streeter 1988). In intercropping systems, competition for soil mineral N between legumes and cereals can result in stimulation of biological N 2 fixation and increased harvest of total interplanted crops (Rerkasem et al 1988;Chandel et al 1989;Peoples et al 1995;Elabbadi et al 1996). Both the competition of N from intercropping maize and the improvement of Fe nutrition of peanut could promote N 2 fixation of peanut in this intercropping system.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies of cereal/legume intercropping have shown that the quantity of N fixed by the legume depends on such factors as the morphology, density, and competitive ability of the legume (Ofori & Stern, 1987), the effectiveness of the rhizobia symbiosis and the system of intercropping (Rerkasem, Rerkasem, Peoples, Herridge, & Bergersationen, 1988). Intercropping of grain legumes generally results in the legume deriving a greater proportion of its N from N fixation than when grown alone, but legume dry matter production and N accumulation are usually reduced because of competition from the companion crop (Giller, Ormeshe, & Awah,1991).…”
Section: Introductionmentioning
confidence: 99%
“…Xylem sap was collected either as sap bleeding spontaneously under pressure from the stump of the intact root following decapitation of the shoot (root-bleeding sap), or under mild vacuum applied to freshly-harvested shoot segments (vacuum-extracted sap). The latter technique (Bennet et al, 1927;Bollard, 1953), facilitated the development of the ureide assay of N2 fixation from one with restricted application (glasshousegrown plants, analysis of root-bleeding sap; McClure et al, 1980) to an assay that could be applied to a wide range of species and field environments (Herridge, 1984;Herridge et al, 1987Herridge et al, , 1988aHerridge and Betts, 1985;Norhayati et al, 1988;Peoples et al, 1989a, b;Rerkasem et al, 1988).…”
Section: Xylem N Solutesmentioning
confidence: 99%
“…Peoples et al, 1989b;Rerkasem et al, 1988). In the case of soybean, the following equations are used ): Pyix(%) = 1 .…”
Section: Xylem N Solutesmentioning
confidence: 99%